About Creation of Bogie of the Freight Car - Gerlici, Juraj; Gorbunov, Mykola; Nozhenko, Olena; Pistek, Vaclav; Kara, Sergiy; Lack, Tomas; Kravchenko, Kostiantyn (Communications - Scientific letters of the University of Zilina, 2017)
Analyses of the operating problems of freight car bogies are carried out, as well as the reasons resulting in deterioration of the dynamic characteristics of modern bogies are specified. The main directions of modernization of existing bogie structures and the creation of fundamentally new designs of the bogies are planned. It is reasonable to design a bogie based on hire and using the multifunctional modules and pre-stressed structures. It would allow to reduce the weight of bogies, improve their strength and dynamic properties, and increase the speed of movement. Design solutions for improving the strength and dynamic properties of bogies implementing these principles, are proposed.